2021
DOI: 10.3390/s21041492
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Applications of Convolutional Neural Network-Based Computer Vision Systems in Animal Farming: A Review

Abstract: Convolutional neural network (CNN)-based computer vision systems have been increasingly applied in animal farming to improve animal management, but current knowledge, practices, limitations, and solutions of the applications remain to be expanded and explored. The objective of this study is to systematically review applications of CNN-based computer vision systems on animal farming in terms of the five deep learning computer vision tasks: image classification, object detection, semantic/instance segmentation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 175 publications
(410 reference statements)
0
67
0
Order By: Relevance
“…One challenge in annotating the images recorded in the turkey flock was the quality of the raw data. Although the cameras had a high resolution, and therefore a high number of pixels in an image, a good sampling rate with 25 frames per second, and suitable installation (meaning an appropriate distance between the camera and surface of interest [ 32 ]), several issues were identified that made it difficult to detect injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One challenge in annotating the images recorded in the turkey flock was the quality of the raw data. Although the cameras had a high resolution, and therefore a high number of pixels in an image, a good sampling rate with 25 frames per second, and suitable installation (meaning an appropriate distance between the camera and surface of interest [ 32 ]), several issues were identified that made it difficult to detect injuries.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, 132 images (20 images from 12 different recording days) were randomly selected, rated by the human observers, and tested for pixel-exact agreement. To examine the performance of the assessment and the segmentation, the intersection over union (IoU) was calculated whereby IoU serves as a standard performance measure for segmentation [ 31 ] and evaluates the deviation between ground truth and predicted areas [ 32 ].…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
“…Traditional image augmentation methods include rotating, flipping, scaling, cropping, etc. [ 22 ]. Because traditional data augment methods easily cause over fitting and under fitting, we present a GAN-based method for Martian rock image data generation, which can generate a large amount of true, diverse Mars images just by training with a few Martian rock images.…”
Section: Building Gmsrimentioning
confidence: 99%
“…Modern dairy farms continue to grow in herd size and technology adoption for maintaining or improving the production and labor efficiencies needed to feed the growing human population [ 1 ]. The U.S. is the largest dairy producer in the world with 9.39 million milking cows on farms, producing 101.25 million metric tons of milk in 2020 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early strategies for monitoring ingestive behavior relied on observation by technicians [ 8 ], to obtain precise individual information on a few animals but is costly and impractical for monitoring large herds [ 9 ]. Imaging methods combined with image processing algorithms or deep learning techniques may provide contactless and non-invasive measures and potentially automate the detection process [ 1 ]. However, high-quality images/videos are prerequisites for this, and appropriately recording the whole jaw movement process without occlusion within herds could be problematic.…”
Section: Introductionmentioning
confidence: 99%